Specifics of the Mechanism of Civil Regulation of Investment Relations: Russia's Results - BELIKOVA, Ksenia; BADAEVA, Natalia; AKHMADOVA, Maryam; KHOSHOBINA, Nina (Journal of Advanced Research in Law and Economics, 2018)
This article explores specifics of the mechanism of civil regulation of investment relations in the context of Russian private law. The authors analyze the main approaches to determining the nature and structure of the legal regulation mechanism that have been developed by legal theorists. Exploring legal categories (legal norms, legal relations and acts of exercising subjective legal rights and obligations) that underlie the general theoretical construction of the mechanism of legal regulation, this study enables a better understanding of branch features concerning civil law regulation of investment relations in modern conditions. As part of this study, the authors proposed the definitions of the concepts ‘civil remedies’, ‘mechanism of civil law (private law) regulation’, ‘investment legal relations’, which allowed justifying the mechanism of civil law (private law) regulation of investment legal relations as the unity of norms of investment law and legal acts adopted in accordance with them that regulate private autonomous provisions (transaction acts and corporate acts). At the same time, for the integrity of the study, the authors distinguish civil means from actions related to their use by parties of social relations, which means that some of its well-known elements, namely acts of exercising subjective legal rights and obligations and legal relations were ‘cut out’ from the mechanism of civil regulation of social relations. In addition, the authors carried out a detailed analysis of various groups of investment law sources (legislation, international treaties, etc.), since the legal norm is the main legal tool for regulating and guiding the behavior of investors and other participants in such legal relations.